Immobilization of cadmium and lead using phosphorus-rich animal-derived and iron-modified plant-derived biochars under dynamic redox conditions in a paddy soil. (November 2021) - Yang, Xing; Pan, He; Shaheen, Sabry M.; Wang, Hailong; Rinklebe, Jörg
Graphical abstract: Highlights: P-rich biochar was more effective in immobilizing Pb than raw and Fe-rich biochars. Raw and Fe-rich green waste biochars were more feasible for Cd fixation than Pb. Fe modification decreased the efficacy of green waste biochar for Pb stabilization. Green waste biochars could immobilize Cd under both anoxic and oxic conditions. Raw and Fe-rich green waste biochars immobilized Pb under Eh ≤ -300 mV. Abstract: Functionalized biochar has gained extensive interests as a sustainable amendment for an effective remediation of paddy soils contaminated with heavy metals (HMs). We examined the efficiency of pig carcass-derived biochar (P-rich biochar, total P = 8.3%) and pristine (raw biochar, total Fe = 0.76%) and Fe-modified (Fe-rich biochar, total Fe = 5.5%) green waste-derived biochars for the immobilization of cadmium (Cd) and lead (Pb) in a paddy soil under pre-defined redox conditions (Eh, from -400 to +300 mV). Average concentrations (μg L -1 ) of dissolved Cd increased under reducing conditions up to 10.9 in the control soil, and decreased under oxidizing conditions to below the detection limit (LDL = 2.7) in the raw and Fe-rich biochar treated soils. Application of the raw biochar decreased the concentrations of dissolved Cd by 43–59% under Eh ≤ -100 mV, compared to the non-treated control, which was more effective than the Fe-rich biochar (31–59%) and the P-rich biochar (8–19%). The immobilization of Cd under low Eh might be due to its precipitation with sulfide (S 2- ), whereas its immobilization under high Eh might be due to the associated increase of pH. Concentrations (μg L -1 ) of Pb ranged from 29.4 to 198.2 under reducing conditions, and decreased to LDL (12.5) under oxidizing conditions. The P-rich biochar was more effective in immobilizing Pb than the raw and Fe-rich biochars, particularly under Eh ≤ 0 mV (55–82%), which might be due to the retention of Pb by phosphates. The raw and Fe-rich biochars immobilized Pb under low Eh (≤ -300 mV), but both biochars, particularly the Fe-rich biochar mobilized Pb under Eh higher than -200 mV, especially at +100 mV, due to the decrease of pH at this point (pH = 6.0 to 6.5). These results improved our understanding of using P-rich and Fe-rich functionalized biochars for the immobilization of Cd and Pb in a paddy soil under stepwise redox changes. The amendment of P-rich pig carcass-derived biochar to paddy soils could be a promising approach for mitigating the risk of Pb for human health and the environment. The raw and Fe-rich green waste-derived biochars can be used for immobilizing Cd and mitigating its risk in paddy soils under both reducing and oxidizing conditions.